The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.stemcr.2014.09.005
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient Differentiation of Human Pluripotent Stem Cells to Endothelial Progenitors via Small-Molecule Activation of WNT Signaling

Abstract: SummaryHuman pluripotent stem cell (hPSC)-derived endothelial cells and their progenitors may provide the means for vascularization of tissue-engineered constructs and can serve as models to study vascular development and disease. Here, we report a method to efficiently produce endothelial cells from hPSCs via GSK3 inhibition and culture in defined media to direct hPSC differentiation to CD34+CD31+ endothelial progenitors. Exogenous vascular endothelial growth factor (VEGF) treatment was dispensable, and endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
271
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 272 publications
(300 citation statements)
references
References 53 publications
(62 reference statements)
18
271
0
Order By: Relevance
“…We previously demonstrated that activation of canonical Wnt signaling in hPSCs in LaSR basal medium generates functional CD34+/CD31+ endothelial progenitors in numerous hPSC lines (Lian et al, 2014). Figures 1A and S1 show schematics of the endothelial differentiation and purification protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that activation of canonical Wnt signaling in hPSCs in LaSR basal medium generates functional CD34+/CD31+ endothelial progenitors in numerous hPSC lines (Lian et al, 2014). Figures 1A and S1 show schematics of the endothelial differentiation and purification protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported a rapid and robust endothelial progenitor differentiation protocol under serum-free conditions, which only employs a Gsk-3β inhibitor in LaSR basal medium (Advanced DMEM/F12, 2.5 mM GlutaMAX and 60 μg/mL ascorbic acid) (Lian et al, 2014). The presence of bovine serum albumin (BSA) in this medium increases the cost, adds xenogenic components, and heightens lot-to-lot variability.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the nature of the serial plating method, where some iPSCs were lost during media replacement due to lack of adherent properties. Efficiency of MSC generation is difficult to establish and reports on iPSC-MSC or embryonic cell conversion often do not include efficiency data [52][53][54][55][56]. However, the flow cytometry results show that the cells that remained attached throughout iPSC-MSC conversion are homogenous and phenotypically similar to CB-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To search for specific miRNAs that affect EC differentiation via glycogen synthase kinase (GSK)-3β inhibition [15], we used a systematic bioinformatics database, TargetScan 6.2 (www.targets can.org). Based on the total context score (4 À 0.1) and the aggregated P CT score (4 0.5), we selected miR-26a, thus conferring stronger regulation than miRNAs with only one binding site ( Fig.…”
Section: Gsk3-β Inhibition Is Sufficient To Induce the Differentiatiomentioning
confidence: 99%
“…The inhibition of GSK-3β in ECFCs leads to increase in ECFC adhesion, survival, proliferation, differentiation, and angiogenic function, which results in accelerating re-endothelialization after vascular injury [12,13]. In addition, GSK-3β inhibition and VEGF exposure in human pluripotent cells induces differentiation of EC [14,15]. However, little is known about the mechanism through which these cells commit to becoming ECs.…”
Section: Introductionmentioning
confidence: 99%